Preharvest Salicylic Acid Incorporated with Calcium Chloride Spray Improves the Postharvest Quality of Thai Dwarf Mulberries (Morus alba) - Youryon, Pannipa; Sangchan, Pra Kaiykarn; Phakawan, Janejira; Ahuja, Anjana Junpatiw; Techavuthiporn, Chairat; Supapvanich, Suriyan (My University, 2026)
The current research evaluated the impacts of preharvest salicylic acid (SA), calcium chloride (CaCl2), and SA incorporated with CaCl2 (SA+CaCl2) sprays on the quality of mulberries. In the preliminary experiment, the mulberries were sprayed with SA (0, 1, and 2 mM) or CaCl2 (0, 0.5, and 1%) before harvest for 5 d. The results indicated that the preharvest application of 1 mM SA or 0.5% CaCl2 resulted in the deceleration of the BrimA (a ripening index) increase and hindered fruit softening during storage at 5 °C for 6 d. In the major experiment, the effects of preharvest sprays of 1 mM SA, 0.5% CaCl2, and SA+CaCl2 for 5 d prior to harvest were investigated. All preharvest treatments delayed fruit darkening and acidity reduction compared to the untreated fruits and did not affect redness. The SA+CaCl2 spray delayed fruit darkening and enhanced firmness compared to the individual sprays. The total soluble solids content and BrimA value of treated mulberries were lower than those of untreated fruits. All treatments improved the antioxidant activity and bioactive compounds compared to the untreated fruits. The ferric-reducing antioxidant potential, DPPH radical scavenging activity, total anthocyanin, and total phenol content were all higher with the SA+CaCl2 preharvest spray than with the SA or CaCl2 spray alone. Thus, the preharvest SA+CaCl2 spray is a promising approach for improving Thai dwarf mulberry postharvest quality.
Keywords: Antioxidants; Bioactive compounds Mulberry cv. ‘Chiang Mai’; Physicochemical quality; Plant regulator